Effectiveness of Self-Talk Training Programs On Athletes Self Confidence and Performance in Sports: A Systematic Literature Review (2015-2025) - Syakir Fathul Mubin; Tite Juliantine; Yusuf Hidayat (Universitas Tadulako, 2025)
Self-confidence is a critical psychological determinant of athletic performance, and self-talk has emerged as one of the most widely applied psychological training program s to strengthen athletes' confidence and competitive effectiveness. This systematic literature review synthesises research published between 2015 and 2025 on the relationship between self-talk, self-confidence, and athletic performance, with particular attention to training program types, underlying psychological processes, and contextual moderators. we conducted a systematic search following PRISMA 2020 guidelines across Scopus, PubMed, and Google Scholar. Of 312 records identified, 32 studies met the PICO-based eligibility criteria and were included in the review. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT) 2018, with most studies meeting the majority of quality criteria and demonstrating acceptable methodological rigour. The findings consistently indicate that positive, motivational, and instructional self-talk enhance athletes' self-confidence, emotional regulation, attentional focus, and competitive performance across various sports contexts. Four key processes were repeatedly identified: attentional control, self-efficacy activation, emotional regulation, and neuromuscular efficiency. Crucially, combined training program s integrating self-talk with imagery produced stronger and more consistent performance improvements than self-talk-only programmes. These findings sug that self-talk is a robust and adaptable psychological strategy, particularly when tailored to task demands and integrated with complementary psychological techniques. Future research should prioritise female and youth athletes, team sport settings, and longitudinal follow-up periods of at least three months to strengthen the research base.